VIRTUAL REALITY BASED HUMAN DIGESTIVE SYSTEM APPLICATION ANDROID - M. Zarkasyi; Amri; Indrawati; Stephen Martin (Bulletin of Engineering Science, Technology and Industry, 2023)
The human digestive system is a system consisting of digestive organs that function to digest food in the human body. The lack of learning media that makes it easy to learn the material of the human digestive system becomes a separate obstacle for users so that research is carried out aimed at developing the learning media of the human digestive system more easily so that it can see the digestive system organs more clearly with virtual. This research uses the Research and Development (R&D) method with the ADDIE development model which consists of four stages namely analysis, design, evaluation and testing. This test is carried out with the appropriateness test conducted on the user testing respondents. The results of respondents' testing on the feasibility of the application of the human body's digestive system using questionnaire data from 40 respondents showed that "Strongly Disagree = 0%", "Disagree = 0.5%", "Neutral = 20.5%", "Agree = 93.5%", "Strongly Agree = 88%". With the application test results using the black box test (Black Box Test) all the menu functions in the application have been successful in accordance with their respective functions. The conclusion of this research is the application of virtual reality digestive system in the human body which is simulated in the digestion of food from the first entry to the exit has been successful as expected.